Stochastic logistic models: a literature review - Martínez-Bernal, Javier; Cuervo-Cruz, Ricardo Andrés; Orjuela-Castro, Javier Arturo (AiBi Journal of Research, Administration and Engineering, 2020)
The present article is done with the aim of to establish the state of the art of location, inventory and routing models with stochastic parameters. The literature reviewed was classified with an operations research approach. A systematic review of the literature in the databases ScienceDirect, ScholarGoogle, SpringerLink, Scopus, SemanticScholar, Scielo, and ResearchGate was done. Through guiding questions, 99 articles were selected, of which 74% is recent literature between 2015 and 2019. Stochastic logistic individual models were classified, a taxonomy with an operations research approach was proposed, from their characteristics, parameters, restrictions, the objective functions and solution methods used. Also, the trends and the future lines of research were identified. As a conclusion new strategies and operating policies that permit improve supply chain performance are identified, also the absence of efficient solution methods has been evident to large instances, according to real-life.
Keywords: Stochastics; Inventory models; Location; Facilities; Multi-echelon; Vehicle Routing Problem; Stochastic models